Clinical Course, Immunogenicity, and Efficacy of BNT162b2 mRNA Vaccination Against SARS-CoV-2 Infection in Liver Transplant Recipients - Eunice X. Tan, MBBS, MMED, MRCP; Wen Hui Lim, MBBS; Elizabeth Thong, MBBS; Jean-Marc Chavatte, PhD; Jinyan Zhang, MBBS; Jonathan Lim, MBBS; Jocelyn Y. Jin, PhD; Daniel R.X. Lim, MBBS; Jaclyn Y.T. Kang, MBBS; Ansel Shao Pin Tang, MBBS; Kai En Chan, MBBS; Caitlyn Tan, MBBS; et al. (Transplantation Direct, 2023)
Background. Immunocompromised individuals have been excluded from landmark studies of messenger RNA vaccinations for severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). In such patients, the response to vaccination may be blunted and may wane more quickly compared with immunocompetent patients. We studied the factors associated with decreased antibody response to SARS-CoV-2 vaccination and risk factors for subsequent breakthrough infections in liver transplant (LT) patients undergoing coronavirus disease 2019 vaccination with at least 2 doses of messenger RNA vaccine from April 28, 2021, to April 28, 2022. Methods. All LT recipients received at least 2 doses of the BNT162b2 (Pfizer BioNTech) vaccine 21 d apart. We measured the antibody response against the SARS-CoV-2 spike protein using the Roche Elecsys immunoassay to the receptor-binding domain of the SARS-CoV-2 spike protein, and the presence of neutralizing antibodies was measured by the surrogate virus neutralization test (cPass) before first and second doses of vaccination and also between 2 and 3 mo after the second dose of vaccination. Results. Ninety-three LT recipients who received 2 doses of BNT162b2 were included in the analysis. The mean time from LT was 110 ± 154 mo. After 2-dose vaccination, 38.7% of LT recipients (36/93) were vaccine nonresponders on the cPass assay compared with 20.4% (19/93) on the Roche S assay. On multivariable analysis, increased age and increased tacrolimus trough were found to be associated with poor neutralizing antibody response (P = 0.038 and 0.022, respectively). The use of antimetabolite therapy in conjunction with tacrolimus approached statistical significance (odds ratio 0.21; 95% confidence interval, 0.180-3.72; P = 0.062). Breakthrough infection occurred in 18 of 88 LT recipients (20.4%). Female gender was independently associated with breakthrough infections (P < 0.001). Conclusions. Among LT recipients, older age and higher tacrolimus trough levels were associated with poorer immune response to 2-dose SARS-CoV-2 vaccination. Further studies are needed to assess variables associated with breakthrough infections and, hence, who should be prioritized for booster vaccination.